Intikhab-e-Kalam : Jameel Mazhari - Jameel Mazhari; Arranged by Muhammad Raza Kazmi (Karachi Oxford University Press, 2008)
This book contains selected poems and lyrics of Jami l Mazhari,one of the most revolutionary and versatile poets. In his poems Mazhari appears dejected as a lover, fiery as a revolutionary, ecstatic as a devotee and indomitable as a worshipper. In all facets of his poetry, he emerges as a thinker, and it is his altruistic attitude to existence which has given an internal cohesion to his varied expression.
Keywords: Urdu Literature - Poetry